Both flowering time and distance to conspecific plants affect reproduction in Echinacea angustifolia, a common prairie perennial. (9th May 2014) - Ison, Jennifer L.; Wagenius, Stuart; Jacquemyn, Hans
Summary In small fragmented plant populations, reproductive failure due to pollen limitation is often attributed to spatial isolation of individuals. While flowering time has been shown to affect seed set, its role in pollen limited fragmented populations is less understood. In this study, we quantified near‐neighbour distances, flowering phenology, and how they interact to affect seed set in individual plants. We followed the daily flowering phenology of over 2400 heads on over 500 Echinacea angustifolia individuals and quantified the resulting seed set during three consecutive flowering seasons. The study was conducted in an experimental plot where we randomized planting locations to eliminate spatial patterns of mate availability which are common in fragmented populations of Echinacea, a self‐incompatible plant. We found that individual flowering time had a larger and more consistent effect on seed set than did spatial location. Seed set in the earliest flowering plants exceeded seed set in the latest by 46–70% in all three years. The role of spatial isolation, characterized both by individual distance to conspecific plants and by location in the plot, was less consistent and showed a weaker relationship with seed set than did flowering phenology. The most isolated plants set 20–27% less seed than the least isolated plants in 2005–2006 with no difference in 2007. In one year, we quantified seed set by floret position within a flowering head. We found significant positional effects; however, effects due to flowering time were much greater. These results were more consistent with the pollen limitation hypothesis than the resources limitation hypothesis. Synthesis. Our results illustrate that flowering time and distance to neighbouring conspecifics can cause reproductive failure in fragmented populations, even in the absence of mate limitation caused by mating incompatibility. These findings suggest that flowering time may be an underappreciated contributor to reproductive failure in small fragmented populations.